Comparison of sprint- and jump-performance outcomes 6 hours following sprint-priming stimuli involving different external loads - Holmberg, P. M.; James, L. P.; Connick, M. J.; Lamont, H. S.; Watts, D. G.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study aimed to (1) compare sprint- and jump-performance outcomes 6 hours following sprint-priming stimuli involving different external loads and (2) investigate whether maximal dynamic strength level influences sprint-priming outcomes.